Evaluation of Risk Factors in Ischemic Stroke - Tariq Mahmood , Muhammad Sohail Anjum , Shahid Iqbal , Naila Kalsoom , Hira Manzoor (Journal of Rawalpindi Medical College, 2013)
Background: To determine the frequency of different risk factors among patients of stroke due to cerebral infarction. Methods: This cross sectional study included 195 patients with stroke due to cerebral infarction. Risk factors leading to cerebral infarction were evaluated . Results: Hypertension (73%) and diabetes (42.5%) were the commonest risk factors seen in patients . Conclusions: Most of the risk factors were modifiable